Expression of virulence genes in group B streptococcus isolated from symptomatic pregnant women with term and preterm delivery - Wahid, Hanan Hamimi; Mustapha Rounal, Puteri Farah Diba; Selvakumaran, Arvind R.; Anahar, Fatin Najihah; Mustafa Mahmoud, Mohammed Imad Al-Deen; Alias, Norsyuhada; Kamarudin, Norhidayah; Baharudin, Roesnita; Husin, Roziah; Ahmad Mustafa, Ahmad Muzamir; Ismail, Hamizah (Malaysian Society for Microbiology, 2022)
Aims: Maternal vaginal Group B Streptococcus (GBS) colonization is considered a risk factor for preterm delivery and, consequently, neonatal infections. Previous studies have portrayed the important roles of these virulence factors, including hemolytic pigment, hyaluronidase (HylB), serine-rich protein (Srr) and bacterial surface adhesion of GBS (BsaB) in mediating GBS colonization and intrauterine ascending infection, causing preterm delivery. This study aimed to investigate the association between mRNA expression of virulence genes in GBS isolates obtained from symptomatic pregnant women and preterm delivery.